Analysis of Problems and Solutions in use of Groundwater in Uzbekistan - D.A. Quvvatov, Ph.D.; N.P. Karimov; J.O. Rozikulov (Zien Journals, 2023)
The article analyzes groundwater, its reserves, quantity, salinity and conditions of use in irrigation on the example of the world and the territory of Uzbekistan. The measures and necessary recommendations for effective use of underground water are presented
Keywords: Groundwater; mineralization; soil; water resources